Opportunistic Infections and Immune-Related Adverse Events Associated with Administering Immune Checkpoint Inhibitors: A Narrative Review - Ranferi Ocaña-Guzmán; Diego Osorio-Pérez; Leslie Chavez-Galan (MDPI AG, 2023)
Manipulating the immune system by blocking the immune checkpoint receptors is the basis of immunotherapy, a relevant tool in current clinical oncology. The strategy of blocking the immune checkpoints (Immune Checkpoint Inhibitors, ICI) consists of using monoclonal antibodies to inhibit the interaction between ligand and inhibitory receptors from triggering a complete activation of helper and cytotoxic T cells to fight against tumour cells. Immunotherapy has benefited patients with diverse cancers such as stomach, lung, melanoma, and head and neck squamous cell carcinoma, among others. Unfortunately, a growing number of reports have indicated that the ICI treatment also can show a dark side under specific conditions; some of the adverse effects induced by ICI are immunosuppression, opportunistic infections, and organ-specific alterations. This review discusses some immunologic aspects related to these unwanted effects.